Employee recruitment and selection strategies in the VUCA Era: A systematic literature review of practices and implementation in companies (2021–2025) - Vicky Purwadi Putra Sawaludin; Alif Vianii Namina (Priviet Social Sciences Journal, 2026)
Rapid changes in the business environment over the past few years have forced many organizations to rethink their employee recruitment and selection processes. This study reviews a range of publications from 2021 to 2025 using a systematic literature review approach to capture the main ideas shaping recruitment and selection practices during this period. Several recurring themes appear in the literature, including the shift toward competency-based assessments, growing reliance on digital tools, and ongoing efforts to maintain fairness and objectivity in evaluating candidates. The review suggests that recruitment and selection processes that remain flexible, especially those combining data-informed decision-making, technological support, and transparent procedures, tend to result in more accurate placement and stronger long-term performance. However, the increasing use of digital systems presents its own challenges, such as the need for HR capacity building and ethical concerns related to algorithmic transparency. Overall, this review provides a clearer picture of how recruitment and selection strategies have evolved in the VUCA era. The findings offer practical insights for organizations seeking to design HR policies that are responsive, ethical, and aligned with the goal of improving workforce quality in the hospitality industry.